1993
DOI: 10.1161/01.res.73.5.935
|View full text |Cite
|
Sign up to set email alerts
|

Changes in creatine kinase M localization in acute ischemic myocardial cells. Immunoelectron microscopic studies.

Abstract: To clarify the changes in creatine kinase M localization along with the progress of myocardial ischemia, immunoelectron microscopic studies were performed using rabbit anti-canine creatine kinase M Fab'-horseradish peroxidase conjugate in 21 dogs. Myocardial ischemia was induced by occlusion of the left anterior descending coronary artery for 15 (n = 5), 30 (n = 5), 60 (n = 5), or 180 (n = 4) minutes. Two dogs were used as normal controls. As we have already demonstrated, most creatine kinase M in normal myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…One may note that upon induction of a contraction, the mobility of this fraction of CK is increased to a value near that of ,B-enolase. This observation is comparable to that of Otsu et al (1993), who noticed that in heart, CK is localized in the A-band, whereas after ischemia this enzyme is more dispersed in the sarcomeres.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One may note that upon induction of a contraction, the mobility of this fraction of CK is increased to a value near that of ,B-enolase. This observation is comparable to that of Otsu et al (1993), who noticed that in heart, CK is localized in the A-band, whereas after ischemia this enzyme is more dispersed in the sarcomeres.…”
Section: Discussionsupporting
confidence: 90%
“…The MM-CK is cytosolic; a small fraction of this enzyme is bound specifically to the M-line structure of the sarcomeres (Wallimann and Eppenberger, 1985), and another fraction seems to be loosely bound to other sites in the sarcomeres. The exact localization of this loosely bound MM-CK is controversial, as Otsu et al (1989as Otsu et al ( , 1993 observed a localization in the whole A-band, whereas Wegmann et al (1992) observed this isoform both localized at the M-line and highly confined to the I-band.…”
Section: Introductionmentioning
confidence: 99%
“…Like cTnI, CK-MB is a well-known marker for MI; it is even more specific to cardiac muscle than to skeletal muscle. 38 Low-density lipoprotein oxidizability was increased, but not to the level of statistical significance, after the induction of hypercholesterolemia and MI. Hypercholesterolemia is associated with increased production of ROS and increased oxidation of LDL cholesterol.…”
Section: Experimental Induction Of MI By Cholesterol and Isoproterenolmentioning
confidence: 91%
“…Although marked reductions in total CK activity reduce myocardial contractile reserve (22,31), normal resting levels of function can be maintained in the face of substantial reductions in total CK (31). At the myofibrillar level, microcompartmentation of CK may play an important role in its functional coupling to myofibrillar ATPase (22,27,42,47). Additional issues relate to possible reductions in the activity of normally functional myofibrillar CK due to limited substrate (ADP) availability (19) and to effects of flow reduction on other myofibrillar components (15).…”
Section: Reduced Myofibrillar Ck Activitymentioning
confidence: 99%